Correlation development for Nusselt number and friction factor of a multiple type V-pattern dimpled obstacles solar air passage. (August 2017) - Kumar, Anil; Kumar, Raj; Maithani, Rajesh; Chauhan, Ranchan; Sethi, Muneesh; Kumari, Anita; Kumar, Sushil; Kumar, Sunil
Abstract: This article presents the outcome of experimental study of Nusselt number ( N u r s ) and friction factors ( f r s ) in a solar air passage with multiple type V-pattern dimpled obstacles. Investigation has been performed to examine the thermal and hydraulic data from a solar air passage with multiple type V-pattern dimpled obstacles on the heated wall. The Reynolds number ( R e ) base on the hydraulic diameter of the solar air passage varied from 5, 000 to 17, 000, relative dimpled obstacles width ( W c / W d ) varied from 1.0 to 6.0, ratio of dimpled depth to print diameter ( e d / d d ) from 0.50 to 2.0, relative dimpled pitch ( P b / e d ) from 8.0 to 11.0, relative dimpled height ( e d / D h ) of 0.037 and the angle of attack ( α a ) varied from 35° to 75°. The optimum data of thermal and hydraulic performance obtained at W c / W d = 5.0, e d / d b = 1.0, P b / e d  = 9.0, e d / D h  = 0.037 and α a  = 55°. The current study shows that the thermal hydraulic performance of multiple type V-pattern dimpled obstacles pattern is around 7.0% higher as compared to other obstacles shapes solar air passage. Correlations of N u r s as well as f r s are established in term of R e and geometrical parameters of multiple V-pattern dimpled obstacles solar air passage can be used to predict the values of N u r s and f r s with considerably good accuracy. Highlights: Thermal performance multiple V-pattern dimpled obstacles solar air passage are investigated. Significant enhancement thermal hydraulic performance as compared to smooth passage. Correlations were developed for Nusselt number and pressure drop. Correlations can predict the Nusselt number and pressure drop with ±10% deviation.